PENGEMBANGAN MODEL AUTO SAMPLING DISSOLUTION TESTER BERBASIS PLC DENGAN KENDALI SMART PHONE - Wisnu Hendri Mulyadi; Sila Wardono, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Dissolution tester is a laboratory tool in the pharmaceutical field that serves to determine the process of dissolving active substances or compounds (drugs) in solvent media. Basically, this dissolution tester tool operates manually with the help of an operator. With the auto sampling dissolution tester tool, it is hoped that it can make it easier for operators who previously operated the dissolution tester manually to be automatically or remotely via a smartphone with the help of PLC (Programmable Logic Control) and ESP32. ESP32 here serves to connect program commands from PLC to smartphones with the Modbus RTU communication protocol. The research method used Based on the tests that have been carried out, automatic sampling and remote operation via a smartphone can work well according to the job description with the help of PLC and ESP32 programs. However, each process stage indicator contained in the smartphone with the original tool with Modbus RTU communication has a standard response with a time difference of about 3-4 seconds. Thus, the auto sampling dissolution tester made with a PLC program can make it easier for operators to operate the dissolution tester.